1990
DOI: 10.1017/s0022215100113428
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation in chronic Reinke's oedema

Abstract: In evaluating the long term results of surgical treatment of Reinke's oedema, there has been found to be a high incidence of recurrence. The recurrence rate is significantly lower amongst those patients who gave up smoking after treatment. A group of patients with chronic Reinke's oedema were followed for six months. Maximum efforts were made to help the patients to stop smoking. Twenty-nine patients entered the study, but only eight of them (28 per cent) refrained from smoking; all were women (39–70 years) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Patients should be encouraged to continue refraining from smoking after the operation to prevent recurrence. 3 In 2000, Sant'Anna and Mauri 5 first introduced the microdebrider system in functional surgery for Reinke's edema. From the experience gained from 5 cases, they suggested that the microdebrider is less invasive than classic methods because the suction pressure needed to remove the degenerated lamina propria is lower with the microdebrider than with classic methods.…”
Section: Resultsmentioning
confidence: 99%
“…Patients should be encouraged to continue refraining from smoking after the operation to prevent recurrence. 3 In 2000, Sant'Anna and Mauri 5 first introduced the microdebrider system in functional surgery for Reinke's edema. From the experience gained from 5 cases, they suggested that the microdebrider is less invasive than classic methods because the suction pressure needed to remove the degenerated lamina propria is lower with the microdebrider than with classic methods.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest a possible neurological effect of nicotine (or other chemical components of tobacco) on the voice 15 . Furthermore, on evaluating the long term results of microlaryngeal surgery in patients with Reinke's oedema, a lower recurrence rate was found in patients who ceased smoking post-operatively 16 . Hence, oedematous vocal fold changes are not an unusual finding in a smoker.…”
Section: Discussionmentioning
confidence: 98%
“…Another 52 cases properly maintained the advice and their voice was fine up to the last follow-up. 33 V.…”
Section: Discussionmentioning
confidence: 99%